(untitled) - Keay, John (London, 1997)
In the East, as recently as 1930, half the world's population was subjected to Dutch, British, French or American colonial rule. Two generations later the West's empires in the East are extinct. Instead, the Orient has become the "Pacific miracle", a catch phrase for all things modern and dynamic. In this survey, John Keay draws on the writing and reminiscences of contemporaries, both rulers and ruled, to chart the extinction of empire. From the 1930 surrender of Weihaiwei ("the other Hong Kong") to the 1997 return of Hong Kong itself, he explores how the shared experiences of recession and war drew the very different empires of the Far East together. The author argues that the imperial construct simply became outdated. Delving into the origins and operation of empire in the Far East, he discovers a continuum of economic and commercial growth. The book covers such "backwaters of empire" as Bali, Borneo and the Yangtze to the "show-pieces" of Singapore, Manila and Saigon, and such bizarre imperial personalities ranging from Douglas MacArthur to Dirk Bogarde. They are confronted by an array of flamboyant nationalists including Ho Chi Minh, Sukarno and Magsaysay. Between Somerset Maugham's Malaya and Graham Greene's Vietnam, the West's attitudes to empire are seen to change; but the subject peoples of the East it is Japan's brief triumph in World War II and Mao's victory in China which cleared the road to independence.
Keywords: Colonies,Decolonization,Decolonization,East asia,Southeast asia; History,History,History,History,History; Asia,East asia,Southeast asia